STANZA SYSTEMS IN IQBOL MIRZO'S POETRY (Scientific journal of the Fergana State University, 2026)
This article examines the role and significance of stanzaic structures in Iqbol Mirzo's poetry. The poet effectively utilizes stanza forms ranging from couplets to twelve-line stanzas, ensuring diversity in rhyme schemes and metrical patterns. This technique enhances the expressiveness of thought and the lyrical quality of his works.